Anticipation for Customer Analytics - Şenvar, Özlem; Yel, Necla; AKBURAK, DİLEK (My University, 2019)
In the digitalization era, enterprises are required to proactive customer relationships via analytical techniques to execute customer treatment strategies based on predictive analytics drawing on a wealth of data about customer behaviors. Nowadays, predictive analytics with automatic decision making concepts are integrated for better understanding preferences of customers, segmenting customers, promoting right products to right customers, improving customer experience, and driving revenue. Customer value anticipation becomes inevitable for understanding customer requirements and expectations. Anticipation can provide capacities in shaping customer perceptions and expectations to make sense of novelty by enlarging and enhancing the analytical and operational approaches to incorporate decision making. In this regard, customer analytics is handled within the perspective of the process by which data from customer behavior utilized to make key business decisions through market segmentation and predictive analytics in order to maximize organizational throughput and maintain long lasting relationships with customers. From this standpoint, this study aims to provide an overview for customer analytics considering anticipation, customer experience and big data analytics involving strategic decision making processes for customer loyalty and relationships. Moreover, customer experience quality is discussed for anticipating customer expectation.
Keywords: Anticipation; Big Data Analytics; Decision Making; Customer Value; Customer Journey